Sea Restoration and Assessment of Ecosystem in Ningbo City. Issue 1 (March 2021) - Liu, Hongdan; Jin, Xinfei; Shen, Chen; Ying, Hong; Wu, Weifei; Zhou, Xuerong; Liu, Xu; Dong, Haiyang
Abstract: From the perspective of the demand of marine ecosystem service function, this paper collects, sorts out and analyzes the marine ecological restoration related work by reclamation survey, mainland coastline survey, island coastline survey, blue bay application, coastal zone restoration project, ecological assessment and restoration of reclamation projects in counties (cities and districts). The successful experience of marine ecological restoration is analyzed, summarized and explored to present a relatively complete and typical marine ecological restoration scheme. Through the case study of typical ecological restoration, the optimized marine ecological restoration procedure is established. According to the development status and problems of different sea areas and coastal zones, the most suitable marine ecological restoration scheme is found, so as to solve specific marine environmental problems, and provide case reference and theoretical basis for subsequent marine ecological restoration.